2020
DOI: 10.3390/nu12082467
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake, Nutritional Adequacy and Food Sources of Total Fat and Fatty Acids, and Relationships with Personal and Family Factors in Spanish Children Aged One to <10 Years: Results of the EsNuPI Study

Abstract: We aimed to determine the usual intake of total fat, fatty acids (FAs), and their main food sources in a representative cohort of the Spanish pediatric population aged 1 to <10 years (n = 707) who consumed all types of milk and an age-matched cohort who consumed adapted milk over the last year (including follow-on formula, toddler’s milk, growing-up milk, and fortified and enriched milks) (n = 741) who were participants in the EsNuPI study (in English, Nutritional Study in the Spanish Pediatric Population).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…ALA intake was below the recommendation in 50% of studies. Daily EPA + DHA intake ranged from 24.7 to 152 mg and was below the FAO/WHO recommendation of 100 mg/day in 7 of the 10 studies for which these data were recovered, except two local studies done in Vancouver (Coastal area in Canada) [49,52] and one subnational study done in urban areas in Spain [89] with daily intakes of 100, 152 and 130 mg, respectively. EPA + DHA consumption was below the EFSA recommendation (250 mg/day) in all studies.…”
Section: Children 2-3 Yearsmentioning
confidence: 84%
See 3 more Smart Citations
“…ALA intake was below the recommendation in 50% of studies. Daily EPA + DHA intake ranged from 24.7 to 152 mg and was below the FAO/WHO recommendation of 100 mg/day in 7 of the 10 studies for which these data were recovered, except two local studies done in Vancouver (Coastal area in Canada) [49,52] and one subnational study done in urban areas in Spain [89] with daily intakes of 100, 152 and 130 mg, respectively. EPA + DHA consumption was below the EFSA recommendation (250 mg/day) in all studies.…”
Section: Children 2-3 Yearsmentioning
confidence: 84%
“…EPA + DHA intake ranged from 30 to 144 mg and was below the FAO/WHO recommendation of 175 mg per day in all 11 studies for which DHA data was recovered for 5-7 years old children, done in 10 countries. Among this age group, three studies in Europe reported intakes which did not meet the recommendation for total and saturated fat (too high), and ALA and DHA (too low) [79,82,89], despite having intakes of LA within 2-4% of energy.…”
Section: Children 3-5 Yearsmentioning
confidence: 98%
See 2 more Smart Citations
“…On the contrary, research about feeding practices in Spain has been mostly focused on children above two years of age and adolescents (e.g., [ 56 , 57 , 58 ]). Only a few studies have included infants and toddlers below 18 months, but they were focused on nutrient intake and adequacy [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%